Interscan reproducibility of quantitative coronary plaque volume and composition from CT coronary angiography using an automated method - Schuhbaeck, Annika; Dey, Damini; Otaki, Yuka; Slomka, Piotr; Kral, Brian G.; Achenbach, Stephan; Berman, Daniel S.; Fishman, Elliott K.; Lai, Shenghan; Lai, Hong (European Radiology, 2014)
Quantitative measurements of coronary plaque volume may play a role in serial studies to determine disease progression or regression. Our aim was to evaluate the interscan reproducibility of quantitative measurements of coronary plaque volumes using a standardized automated method.Coronary dual source computed tomography angiography (CTA) was performed twice in 20 consecutive patients with known coronary artery disease within a maximum time difference of 100 days. The total plaque volume (TP), the volume of non-calcified plaque (NCP) and calcified plaque (CP) as well as the maximal remodelling index (RI) were determined using automated software.Mean TP volume was 382.3 ± 236.9 mm(3) for the first and 399.0 ± 247.3 mm(3) for the second examination (p = 0.47). There were also no significant differences for NCP volumes, CP volumes or RI. Interscan correlation of the plaque volumes was very good (Pearson's correlation coefficients: r = 0.92, r = 0.90 and r = 0.96 for TP, NCP and CP volumes, respectively).Automated software is a time-saving method that allows accurate assessment of coronary atherosclerotic plaque volumes in coronary CTA with high reproducibility. With this approach, serial studies appear to be possible.Reproducibility of coronary atherosclerotic plaque volume in coronary CTA is high. Using automated software facilitates quantitative measurements. Serial studies to determine progression or regression of coronary plaque are possible.
EVALuna2:11992